Предмет: Алгебра,
автор: goloviu
Решите уравнение
Ответы
Автор ответа:
0
(√х)²=(х-в)²
х=х²-2хв+в²
х²-х(2в+1)+в²=0
х1,2=(2в+1)/2+/-√(2в+1)²/4-в² =(2в+1)/2+/-√(4в²+4в+1-4в²)/4
х1=(2в+1)/2+√(4в+1)/2=(2в+1+√4в+1)/2
х2=(2в+1-√4в+1)/2
х=х²-2хв+в²
х²-х(2в+1)+в²=0
х1,2=(2в+1)/2+/-√(2в+1)²/4-в² =(2в+1)/2+/-√(4в²+4в+1-4в²)/4
х1=(2в+1)/2+√(4в+1)/2=(2в+1+√4в+1)/2
х2=(2в+1-√4в+1)/2
Похожие вопросы
Предмет: Химия,
автор: sty743383
Предмет: Математика,
автор: ekimova228
Предмет: Русский язык,
автор: kiasharlan
Предмет: Химия,
автор: Аноним
Предмет: Математика,
автор: artyom0703